1985
DOI: 10.3354/meps024129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and salinity on the toxicity of arsenic to three estuarine invertebrates (Corophium volutator, Macoma balthica, Tubiflex costatus)

Abstract: Acute toxicity of pentavalent arsenic to 3 estuarine invertebrates (Corophium volutator, Macoma balthica, Tubitex costatus) has been studied at 3 temperatures (5, 10, 15OC) and a range of salinities (5 to 35 %o, in 5 %O increments), at time intervals u p to 384 h. Median survival times decreased as temperature and concentrat~on of arsenic increased, but salinity changes had no significant effect. From analysis of variance, significant factors and their interactions were ~n c l u d e d in response surface model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…In contrast, arsenic toxicity is not affected by salinity, despite the most toxic form arsenite (3+) predominating over arsenate (5+) at low salinities ( Fig. 3; Bryant, Newbery, McLusky, & Campbell, 1985a). However, the authors of this study measured the As anionic form instead of the cationic one, and so it is likely that the method used to measure the anionic form may have affected the As bioavailability and also influenced osmoregulation.…”
Section: Toxic Metalsmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, arsenic toxicity is not affected by salinity, despite the most toxic form arsenite (3+) predominating over arsenate (5+) at low salinities ( Fig. 3; Bryant, Newbery, McLusky, & Campbell, 1985a). However, the authors of this study measured the As anionic form instead of the cationic one, and so it is likely that the method used to measure the anionic form may have affected the As bioavailability and also influenced osmoregulation.…”
Section: Toxic Metalsmentioning
confidence: 70%
“…As far as toxicity of toxic metals to marine organisms is concerned, Sullivan (1977) reported that the mortality of the crab Paragrapsus gaimardii induced by cadmium was greater at 19°C compared to 5°C. Bryant et al (1985a) reported that arsenic toxicity to three estuarine bottom feeder invertebrates (Corophium volutator, Macoma balthica and Tubifex costatus) increased as temperature and concentration of arsenic increased. Bryant et al (1985b) evaluated the acute toxicity of nickel and zinc to two estuarine invertebrates (Corophium volutator and Macoma balthica) at 5, 10 and 15°C, and found that an increase in temperature caused a decrease in survival for C. volutator with both metals, and for M. balthica with zinc but not with nickel.…”
Section: Impacts On Ecosystemmentioning
confidence: 98%
“…As shown in this study and others, if survival, condition index or fecundity are taken into account, aquatic invertebrates may be considered as remarkably resistant to As (Bryant et al 1985;Sanders 1986;Sanders et al 1988;Madsen 1992). However when attention is directed towards biological mechanisms at the cellular level, changes may be observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of oiled Fucus algae, L. lineatus fed and incorporated large quantities of oil in the gut, chloragocytes became blackened, and apparently transformed the oil through metabolic processes. Bryant et al (1985) explored the variability of the toxicity of arsenic to three estuarine invertebrates including the European tubificine Heterochaeta costata (as Tubifex costatus). The tubificine survived for more than 384 h at all combinations of temperature and salinity in a concentration of 250 ppm As.…”
Section: Chronic Estuarine and Marine Water-only Testsmentioning
confidence: 99%
“…Chapman et al (1982b, c) reported 96-h LC 50 values for Tectidrilus verrucosus (as Limnodriloides), Tubificoides fraseri (as T. gabriellae) and Monopylephorus cuticulatus, and showed that similar to freshwater species, the presence of sediments increased tolerance to both chemicals and environmental factors. Bryant et al (1985) calculated the Median Lethal Tolerance of Heterochaeta costata (as Tubifex costatus) to pentavalent As (as sodium arsenate) using sterile sand as a substrate, in a combination of conditions of temperature and salinity. Worms did not survive more than 24 h in salinities above 25‰.…”
Section: Acute Estuarine and Marine Sediment Testsmentioning
confidence: 99%